Impact of teacher communication skills on students’ classroom engagement in mathematics learning - Chianson-Akaa, Martha Mimi; Achor, Emmanuel Edoja; Rott, Benjamin (Teaching Mathematics and Computer Science, 2025)
The study investigated teachers’ communication skills in relation to students’ classroom engagement in mathematics learning. The study area is Makurdi Local Government Area in Benue State, Nigeria. This study adopted a cross-sectional research design. A sample of 34 teachers and 204 students were drawn from twenty schools. Two researcher-structured instruments were used for data collection: Mathematics Teacher’s Communication Skills Questionnaire (MTCSQ) and Students’ Engagement in Mathematics Questionnaire (SEMQ). Descriptive statistics, analysis of variance, and independent t-tests were used to address the research questions and test the hypotheses. It was found that there is significant difference among the mean ratings on behavioural, and emotional engagements of students in mathematics classes taught by teachers with poor, fair, and good communication skills. There is no significant difference among the mean ratings on combined and cognitive engagements of students in mathematics classes taught by teachers with poor, fair, and good communication skills. Equally found was that the differences between male and female students’ mean engagement in mathematics for poor, fair, and good communication skill classes were not statistically significant. It was then recommended that teacher communication skills should be fashioned in ways to accommodate and strengthen each component of students’ engagement. Subject Classification: 97C70